RFID Technology: Perspectives and Technical Considerations of Microstrip Antennas for Multi-Band RFID Reader Operation - Mobashsher, Ahmed Toaha; Islam, Mohammad Tariqul; Misran, Norbahiah (IntechOpen, 2011)
None